Current trends of the serve skill in relation to the in-game roles of the elite volleyball players: Comparison between genders - Barzouka, K.; Sotiropoulos, K.; Drikos, S.; Kitsiou, A.; Angelonidis, Y. (Journal of Human Sport & Exercise, 2021)
The aim of this study was to investigate the current trends of the serve skill for each one of the in-game roles of the players for both genders in high-level volleyball. The serve actions of male (M) and female (F) elite players from 20 volleyball games (M = 10, F = 10) of the final phase World League 2018 were assessed. The analysed variables were comprised of the serve type, the serving area (SA), the serve direction, the in-game role of the server and the serve performance. Results showed that men mainly preferred the power jump serve from the areas behind zones 1 (SA1) and 6 (SA6), while they directed them to the back of the court and made more mistakes than women. Women preferred the floating jump serve directed to the left central part of the court. Regarding the in-game roles of the men, the receivers-attackers and the middle-attackers carried out their serves from SA1 and SA6 more frequently compared to women who preferred to use the serve area behind zone 5 (SA5) more frequently than men. Additionally, women opposites and setters chose to use the SA1 more frequently and the SA5 and SA6 less frequently in comparison to their men counterparts.